2019
DOI: 10.1177/0192513x19842598
|View full text |Cite
|
Sign up to set email alerts
|

The Good Parent: Southern Italian Mothers’ Conceptualization of Good Parenting and Parent–Child Relationships

Abstract: Thirty mothers, ranging in age between 30 and 46 years, participated in seven focus groups aimed at analyzing perceptions and ideas of the characteristics of a good parent and parent–child relationship in southern Italy (Sicily). The discussions were transcribed and analyzed using the constant comparative analysis approach. Two major themes, discipline and affection, emerged from the discussions about the idea of a good parent, with seven further subthemes. In defining good parenting beliefs and practices, Sic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…This result needs to be referred also to the cultural context of southern Italy, where the data were collected. Southern Italian people are often socialized into taking care of the other family members, and tend to emphasize the importance for their happiness, of the others' satisfaction, including partners, maybe as a consequence of familistic beliefs that are predominantly diffused in those settings (e.g., Campos, Ullman, Aguilera, & Dunkel Schetter, 2014; Lo Cricchio, Lo Coco, Cheah, & Liga, 2019; Taylor, Larsen‐Rife, Conger, & Widaman, 2012). Therefore, personal and partners' BNF and well‐being are associated: The more individuals show satisfaction in their needs and well‐being, measured in terms of having purposes in life, experiencing personal growth, and self‐acceptance, the more their partners show higher levels on the same dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…This result needs to be referred also to the cultural context of southern Italy, where the data were collected. Southern Italian people are often socialized into taking care of the other family members, and tend to emphasize the importance for their happiness, of the others' satisfaction, including partners, maybe as a consequence of familistic beliefs that are predominantly diffused in those settings (e.g., Campos, Ullman, Aguilera, & Dunkel Schetter, 2014; Lo Cricchio, Lo Coco, Cheah, & Liga, 2019; Taylor, Larsen‐Rife, Conger, & Widaman, 2012). Therefore, personal and partners' BNF and well‐being are associated: The more individuals show satisfaction in their needs and well‐being, measured in terms of having purposes in life, experiencing personal growth, and self‐acceptance, the more their partners show higher levels on the same dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…Scenarios that idealise mothering and the transition period are guided by normative ideas of what a good mother is, with no acknowledgement of how time or contexts shape new mothers' constructions of mothering in the immediate postnatal period, or how they adjust to the transition period between birth and early childhood. The ways that new mothers navigate this extended postnatal period shows how they construct mothering identities which respond to perceived pressures to balance their own, as well as societal, expectations to present themselves to the world in particular ways (Lo Cricchio, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…According to theory, role is a form of real behavior (Toscano et al, 2020). So what is needed more by early childhood is the real behavior of parents, not the material (Lo Cricchio et al, 2019). One of the important things to develop early is about life skills.…”
Section: Income Levelmentioning
confidence: 99%
“…A role is a set of interpersonal behaviors, traits, activities related to the person in certain positions and, situations (Hind et al, 2019). The family is the first and foremost place for children to get an education, this process requires an important role from parents (Lo Cricchio et al, 2019). Regarding those ideas, it can be concluded that education in early childhood is the prority and started since the child was born.…”
Section: Introductionmentioning
confidence: 99%